Financial repression in India. - Grewal, Bilkees (2007)
As the economy grows and becomes more refined the banking sector has to develop at the same time in such a manner that it supports and stimulates the growth. With increasing global integration, the Indian banking system and financial system on a whole has to be strengthened so as to be able to compete. Since more than a decade India has had financial sector reforms during which there has been considerable transformation and liberalization of the whole financial system. Repressionist policies have played a major role in the banking sector since liberalisation. This study aims to analyze the effects of financial repression on the financial depth, financial development and economic development of India.